Pengaruh Free Cash Flow, Kepemilikan Institusional, Kepemilikan Manajerial, Arus Kas Operasi Dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Ida Ayu Made Ratih; Ida Ayu Surasmi (Lembaga Penelitian, Universitas Warmadewa, 2025)
This study aims to analyze the effect of free cash flow, institutional ownership, managerial ownership, operating cash flow, and company size on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study uses a quantitative method with secondary data obtained from the annual financial reports of consumer goods sector manufacturing companies listed on the IDX. The population in this study were all consumer goods sector manufacturing companies, with a sample of 44 companies selected using the purposive sampling method based on certain criteria. The data were analyzed using multiple linear regression with the help of SPSS for Windows to test the relationship between independent variables and dividend policy as the dependent variable. The results showed that free cash flow and institutional ownership had a positive and significant effect on dividend policy, while managerial ownership, operating cash flow, and company size did not have a significant effect. This finding indicates that dividend policy is more influenced by cash availability factors and institutional investor ownership.